Extraction and Identification of Alkaloids of the Ipomoea fistulosa (Aguapei or Mandiyurá) of Argentina - Cholich, Luciana Andrea (2007)
The classical toxic effect produced by this Ipomoea fistulosa is due to the accumulation of oligosacharides in various tissues cell cytoplasm, mainly nervous, liver and lymphatic tissues, that leads to the cell vacuolitation. These effects are attributed to the presence of substances called swansonina and calisteginas in the vegetables, which produce inhibition of enzymes liposomales responsible for the metabolic carbohydrates. In natural conditions, the plant is not consumed by the animals. Its consumption occurs alone in determined times of year, for lack of sufficient pasture and it is more frequent in young animals. Since standard literature does not register any data on the chemical analysis of the kind Ipomoea, we report here the results on the extraction, isolation and spectroscopic identification of the present alkaloids in this plant.